Hospitalization costs for children with pneumonia in Shanghai, China from 2019 to 2020 - Jing Wang; Zhen-Hui Xu; Jin Lu (Taylor & Francis Group, 2022)
Pneumonia is the leading cause of death in children under 5 years of age worldwide. In this study, we primarily analyzed the hospitalization costs for children diagnosed with pneumonia in one of the leading public hospitals in Shanghai, China. Furthermore, factors affecting the hospitalization costs for children with pneumonia were evaluated. Data on case diagnosis, hospitalization time, age and various hospitalization expenses were collected. Total hospitalization expense for the 149 cases was $177,750, with an average total cost of $1,193 per person and an average out-of-pocket cost of $642. The highest per capita expenses included fees for laboratory diagnosis ($418), general medical service ($235), western medicine ($253), and antibacterial drugs ($158). The leading diagnosis was bronchopneumonia, with 68 (46%) cases, an average hospital stays of 7.4 days, and average hospitalization expenses of $1,068. Considering the high burden of pneumonia in children, hospitals and governments must make more reasonable use of limited resources of the medical system. At the same time, various types of medical insurance should be added into the children's medical security system, encourage vaccination with pneumonia vaccines (13-valent pneumococcal conjugate vaccine and 23-valent pneumococcal polysaccharide vaccine), and ensure that more children benefit from the vaccine by including it in the national immunization program.